Case 3723: Bolitophagus cornutus Fabricius, 1801 (currently Bolitotherus cornutus) (Insecta: Coleoptera: Tenebrionidae): proposed conservation of the specific name - Bousquet, Y; Bouchard, P (Bulletin of Zoological Nomenclature, 2017)
The purpose of this application, under Article 23.9.3 of the Code, is to conserve the specific name Bolitophagus cornutus Fabricius, 1801 (currently Bolitotherus cornutus) for a common and well-known North American darkling beetle by giving it precedence over its senior synonym Opatrum bifurcum Fabricius, 1798
Keywords: Nomenclature; taxonomy; Coleoptera; Tenebrionidae; Bolitotherus; Opatrum bifurcum; Bolitophagus cornutus; North America